New Insights into Sprout Production from Melon (Cucumis melo L. var. reticulatus) Seeds as By-Product of Fruit Processing - Angelica Galieni; Beatrice Falcinelli; Fabio Stagnari; Eleonora Oliva; Federico Fanti; Maria Chiara Lorenzetti; Paolo Benincasa (Plants, 2025)
Melon is a valuable crop that generates significant by-products during consumption and processing. Among these, seeds are rich in phenolic compounds and might be used to produce sprouts with increased content of these bioactive substances. This study evaluated phenolic compounds (PhCs) in sprouts of two melon cultivars, Thales and SV9424ML, obtained from seeds having different germination speeds, thus harvested at 6 and 14 days after sowing (DAS). A factorial combination of cultivar and harvest time was tested in a completely randomized design with four replicates. Thales produced more ready-to-eat sprouts at 6 DAS than SV9424ML (64.0% vs. 46.7%). Sprouting significantly increased total PhCs content, particularly flavonoids, with Thales showing higher values than SV9424ML (50.2 vs. 32.6 mg kg−1 DW). Phenolic profiles significantly varied among cultivars and harvests. Sprouts at 6 DAS had more total hydroxybenzoic acids and flavonoids, while 14 DAS sprouts were richer in hydroxycinnamic acids. Significant differences between harvest dates were observed in the concentrations of protocatechuic, vanillic (VanA), p-coumaric (p-CouA), ferulic (FerA) acids, and orientin (Ori) for Thales, and of VanA, p-CouA, FerA, and Ori for SV9424ML. Results are encouraging, but future investigations are essential to understand whether these sprouts can be suitable for fresh consumption, food supplements, or phytochemical extraction.